Role of lncRNA BANCR in Human Cancers: An Updated Review - Hussen, Bashdar Mahmud; Azimi, Tahereh; Abak, Atefe; Hidayat, Hazha Jamal; Taheri, Mohammad; Ghafouri-Fard, Soudeh (Frontiers in Cell and Developmental Biology, 2021)
Being located in a gene desert region on 9q21.11-q21.12, BRAF-activated non-protein coding RNA (BANCR) is an lncRNA with 693 bp length. It has been discovered in 2012 in a research aimed at assessment of gene expression in the melanocytes in association with BRAF mutation. Increasing numbers of studies have determined its importance in the tumorigenesis through affecting cell proliferation, migration, invasion, apoptosis and epithelial to mesenchymal transition. BANCR exerts its effects via modulating some tumor-related signaling pathways particularly MAPK and other regulatory mechanisms such as sponging miRNAs. BANCR has been up-regulated in endometrial, gastric, breast, melanoma and retinoblastoma. Conversely, it has been down-regulated in some other cancers such as those originated from lung, bladder and renal tissues. In some cancer types such as colorectal cancer, hepatocellular carcinoma and papillary thyroid carcinoma, there is no agreement about BANCR expression, necessitating the importance of additional functional studies in these tissues. In the present manuscript, we review the investigations related to BANCR expression changes in cancerous cell lines, clinical samples and animal models of cancer. We also discuss the outcome of its deregulation in cancer progression, prognosis and the underlying mechanisms of these observations.